Ancaman Keamanan Atas Investasi China di Israel - Afif, Fadlur Rifki; Machmudi, Yon (UI Scholars Hub, 2021)
The investment made by China in Israel is an effort to realize the Belt and Road Initiative initiated by President Xi Jinping poses a security threat to Israel. The focus of this research lies in the possibility of security threats to the various investments made by China in Israel, causing intervention from America. The method used in this paper is the Qualitative Method (Case Study). The results of this study indicate that the threat to Chinese investment in Israel is only a concern for Israel because China adheres to the 'Zero Enemy' policy.